Passage Number is a Major Contributor to Genomic Structural Variations in Mouse iPSCs. (October 2014) - Liu, Pengfei; Kaplan, Anna; Yuan, Bo; Hanna, Jacob H.; Lupski, James R.; Reiner, Orly
Abstract Emergence of genomic instability is a practical issue in preparing neural stem cells (NSCs) and induced pluripotent stem cells (iPSCs). However, it is still not fully understood what the origins and mechanisms for formation are for the genomic alternations observed. Here, we studied the extent of genomic variation on the scale of individual cells originating from the same animal. We used mouse NSCs grown from embryonic cells and iPSCs generated from embryonic brain cells, B cells or fibroblasts, and performed comparative analysis with cultures of fibroblasts from the same mouse. In the first passage of these cell lines, aneuploidies were only observed for chromosomes 6, 11, 12, 19, and Y, which is overall at a rate lower than previously reported; de novo copy number variations (CNVs) were observed in 4.3% of neural iPSCs, 29% of B cell iPSCs, 10% of fibroblast iPSCs, and 1.3% of neurospheres. In contrast, propagation of these first passage cells to a later passage induced additional aneuploidies and CNVs. Breakpoint sequencing analysis suggested that the majority of the detected CNVs arose by replicative mechanisms. Interestingly, we detected identical de novo CNVs in different single cell colonies that appeared to have arisen independently from each other, which suggests a novel CNV formation mechanism in these cells. Our findings provide insights into mechanisms of CNV formation during reprogramming and suggest that replicative mechanisms for CNV formation accompany mitotic divisions. Stem Cells2014;32:2657–2667